1999 Leverett Graduate Student Merit Awards for - Angkana Thearmontree, DDS, MSD (Blackwell Synergy, 2000)
Angkana Thearmontree, DDS, MSD, MPH Department of Epidemiology Program in Dental Public Health University of Michigan Ann Arbor, MI Nominator: Brian A. Burt, BDS, PhD